A case of intussusception caused by cecal duplication after COVID-19. Issue 3 (9th March 2022) - Satoyoshi, Rika; Kotanagi, Kei; Kichiraku, Takuya; Yoshino, Kei; Kudoh, Kazuhiro; Sawada, Toshiya; Miyazawa, Hideaki; Kotanagi, Hitoshi
Abstract: Coronavirus disease 2019 (COVID-19) was thought to have respiratory symptoms as the main manifestation, but it has become clear that extrapulmonary symptoms such as gastrointestinal disorders also occur. There are several reports of intussusception associated with COVID-19 in children, but these are rare in adults. In this report, we present a case of cystic intestinal duplication that enlarged during the course of COVID-19 treatment and resulted in intussusception. Right hemicolectomy was performed for intussusception due to the cystic lesion. To the best of our knowledge, this is the first resected case of intussusception due to alimentary tract duplication after COVID-19 infection.